DEPENDENCE OF MORPHOMETRIC CHARACTERISTICS OF TURNIP MOTH (AGROTIS SEGETUM) LARVAE ON HOST PLANTS (Scientific journal of the Fergana State University, 2025)
This article examines the dependence of morphometric parameters—body length and body weight variability (expressed as the coefficient of variation, CV)—of the turnip moth (Agrotis segetum) larvae on different host plants (beet, carrot, turnip, radish). The study employed statistical analyses, including the coefficient of variation along with tf and P-values, to assess the degree of genetic and phenotypic variability within larval populations under various crop conditions. The findings indicate that while the variability in body length remains relatively similar across different agroecosystems, significant differences in body weight variability are observed—particularly under turnip and radish conditions, where higher variation was recorded. These results are crucial for understanding the ecological adaptation and population dynamics of the pest, improving monitoring and forecasting within the IPM framework, and developing targeted recommendations for crop management and pesticide application in agricultural practices.